Indolent Propionibacterium acnes infection associated with orthopedic hardware in the ankle: A case report and literature review. Issue 8 (24th June 2019) - Arain, Abdul R.; Sullivan, Connor W.; Angelicola‐Richardson, Kyle; Haddad, Stefanos; Rosenbaum, Andrew
Abstract: Propionibacterium acnes ( P. acnes ) infections of the foot and ankle are very rare and require a unique approach to prevention, diagnosis, and treatment. Clinicians should consider P. acnes as a cause for all late and indolent orthopedic infections, as appropriate surgical and medical management can result in a good outcome. Abstract : Propionibacterium acnes ( P. acnes ) infections of the foot and ankle are very rare and require a unique approach to prevention, diagnosis, and treatment. Clinicians should consider P. acnes as a cause for all late and indolent orthopedic infections, as appropriate surgical and medical management can result in a good outcome.